Analisis Bentuk, Makna, dan Fungsi Variasi Bahasa Otaku Pada Kategori Konten Josei-muke - Untari Widi Hapsari (IZUMI, 2025)
Language has variation due to the diversity of the speakers and their social interactions (Chaer & Agustina, 2004). Language variations can be found in many social groups. Otaku is one of the groups. This research is descriptive-qualitative research that studies otaku language variation in josei-muke contents category. This research aims to describe the word formation, meaning, and function of the language variation. The data were taken from comments on Youtube videos and archived live streaming about josei-muke content. The analysis of its word formation using Tsujimura’s (2014) theory, of its meaning by considering its meaning in dictionaries and other internet sources about otaku language variation on josei-muke contents. Then, the function is described by the result of word formation and meaning analysis. This research found eight types of word formation, which are affixation, compounding, clipping, borrowing, noun formation from renyoukei of verbs, abbreviation, onomatopoeia, and original Japanese words. The meanings can be classified into eight groups, which are type and genre of the content, otaku type, title of the content, role in the content, coupling in the content, technical term, valuation, and expression of feeling. Then, the functions of otaku language variation on josei-muke contents are also found, which are as identity as otaku, to concise speech, to convey information briefly, and to express feelings. gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor